Thermoplastic Starch with Maltodextrin: Preparation, Morphology, Rheology, and Mechanical Properties - Rana, Lata; Kouka, Saffana; Gajdosova, Veronika; Strachota, Beata; Konefał, Magdalena; Pokorny, Vaclav; Pavlova, Ewa; Stary, Zdenek; Lukes, Jaroslav; Patocka, Marek; Hegrova, Veronika; Fortelny, Ivan; et al. (Materials (Basel, Switzerland), 2024)
This work describes the preparation of highly homogeneous thermoplastic starches (TPS's) with the addition of 0, 5, or 10 wt.% of maltodextrin (MD) and 0 or 3 wt.% of TiO2 nanoparticles. The TPS preparation was based on a two-step preparation protocol, which consisted in solution casting (SC) followed by melt mixing (MM). Rheology measurements at the typical starch processing temperature (120 °C) demonstrated that maltodextrin acted as a lubricating agent, which decreased the viscosity of the system. Consequently, the in situ measurement during the MM confirmed that the torque moments and real processing temperatures of all TPS/MD systems decreased in comparison with the pure TPS. The detailed characterization of morphology, thermomechanical properties, and local mechanical properties revealed that the viscosity decrease was accompanied by a slight decrease in the system homogeneity. The changes in the real processing temperatures might be quite moderate (ca 2-3 °C), but maltodextrin is a cheap and easy-to-add modifier, and the milder processing conditions are advantageous for both technical applications (energy savings) and biomedical applications (beneficial for temperature-sensitive additives, such as antibiotics).
Keywords: maltodextrin modification; thermoplastic starch; lower processing temperature; lower viscosity